PENENTUAN DOSIS KOAGULAN PADA PENGOLAHAN AIR MINUM: PENDEKATAN FUZZY BERBASIS DATA DAN PENENTUAN FUZZY SET BERBASIS Z-SCORE - Monica Cinthya; Retno Aulia Vinarti; Nisa Dwi Septiyanti; Cendra Devayana Putra; Erik Rahman; Rifqi Abdillah (Journal of Innovation And Future Technology, 2025)
direct use of raw water has serious health risks. Therefore, various water treatment processes are needed to make the raw water safe for use in domestic purposes. One important stage in such processing processes is coagulation and flocculation, where chemicals (coagulants) are used to remove colloidal particles and form larger floc that can be easily precipitated through sedimentation and filtration. Determination of the optimal coagulant dosage is essential to achieve the desired water quality. However, jer-test problems, the non-linear nature of water, and the complexity of coagulation theory can make it difficult to determine the optimal dose. Therefore, in this study, a system is proposed that uses a data-based fuzzy approach and fuzzy set determination using z-score to study data patterns and relationships between parameters in the coagulation process. The proposed method utilizes a fuzzy approach to address the non-linear nature of water and the complexity of coagulation theory. The system uses the collected data patterns to develop fuzzy models that can predict optimal coagulant doses based on specific conditions. This approach allows the system to learn from existing data and identify patterns of relationships that may be hidden between relevant parameters. The results showed that the proposed system achieved an RMSE value of 0.7639589866827494, while the MSE value was 0.5836333333333333333. This suggests that the system can provide a fairly accurate prediction of the dose of coagulant required in the coagulation process.